Analisis Kesalahan Penggunaan Konjungsi Dalam Karangan Argumentasi Siswa Kelas X Sma N Gondangrejo - Ngalimmudin, Muhammad Ekhwan; , Dra. Atiqa Sabardila, M. Hum (2016)
The purpose of this study is to (1) describe the use of the conjunction errors in argumentation bouquet grade X SMA N Gondangrejo, (2) assess the appropriateness of the use of the conjunction argument essay on grade X SMA N ondangrejo. This type of research is qualitative, descriptive. The data in this research in the form of the conjunction in the essay arguing students. The data source is bouquet this argumentation research students. The technique of data collection by using the techniques of documentation. Data analysis techniques using intralingual and techniques in accordance agih covers the basic techniques in the form of techniques for direct elements or techniques BUL, advanced techniques in the form of lesap engineering, technical change, and expand. The results of the analysis of the use of the conjunction errors in argumentation bouquet shows occur 48 errors. Use of conjunction error koordinative be conjunction and totaled 13 errors, conjunction with numbered 5 errors, the conjunction but numbered 5, conjunction errors while totaling 4 errors, the conjunction is numbered 4 errors, and the conjunction and amounted to 1 error. Use of conjunction error subordinating be the conjunction because numbered 8, conjunction errors so that amounted to 4 errors, conjunction reasons amounted to 3 e Keywords: Essay Argumentation, conjunction Coordinative and Subordinating